(untitled) (INNOTEC, 2019)
Feedlots are plots located in establishments on which bovine cattle is fattened for market by means of the use of concentrated foods. The objective of this work was to characterize watercourses located in decline with respect to the areas where fattening pens are located in terms of nutrient concentrations and of the inputs of solids, through physicochemical analyses, and with regard to ecotoxicity through models of bioassays. To do so, samples were taken from two establishments at three different points of each watercourse: upstream, in front of, and downstream the feedlots. This study did not detect appreciable levels of acute toxicity to Daphnia magna but mild levels of toxicity in both watercourses to Vibrio fischeri and Lactuca sativa consisting on biostimulatory effects. Through physicochemical studies, it was found that in both watercourses the total phosphorus levels exceeded the established values in Decree 253/79, which were present even upstream, but further increasing downstream to the corrals.